2016
DOI: 10.1097/tp.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Myoblast Cell Sheet Implantation Ameliorates Both Systolic and Diastolic Cardiac Performance in Canine Dilated Cardiomyopathy Model

Abstract: BackgroundImproving both systolic and diastolic function may be the most important factor in treating heart failure. In this study, we hypothesized that cell-sheet transplantation could improve these function in the damaged heart.MethodsWe generated a dilated cardiomyopathy model in beagles by continuous ventricle pacing at 240 beats per minute. After 4 weeks, the beagles underwent skeletal myoblast cell sheet transplantation (SMCST) or a sham operation, and rapid ventricle pacing continued for an additional 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…As a potential therapeutic approach, cell‐based therapies have rapidly emerged. Different cell strains used include bone marrow mononuclear cells (BMMCs), G‐CSF‐stimulated autologous CD34 + peripheral blood stem cells (PBSC), embryonic stem cells (ESCs), skeletal myoblast, mesenchymal stem cells (MSCs), endothelial progenitor cells (EPCs), cardiac stem cells and adipose tissue‐derived stem cells, either with the methods of intracoronary (IC) or intramyocardial (IM) injections. Among these cell‐based therapies, bone marrow‐derived mononuclear cells (BMMNCs) are easily obtained and cultured with differentiation capacity .…”
Section: Introductionmentioning
confidence: 99%
“…As a potential therapeutic approach, cell‐based therapies have rapidly emerged. Different cell strains used include bone marrow mononuclear cells (BMMCs), G‐CSF‐stimulated autologous CD34 + peripheral blood stem cells (PBSC), embryonic stem cells (ESCs), skeletal myoblast, mesenchymal stem cells (MSCs), endothelial progenitor cells (EPCs), cardiac stem cells and adipose tissue‐derived stem cells, either with the methods of intracoronary (IC) or intramyocardial (IM) injections. Among these cell‐based therapies, bone marrow‐derived mononuclear cells (BMMNCs) are easily obtained and cultured with differentiation capacity .…”
Section: Introductionmentioning
confidence: 99%
“…Heart failure, especially due to DCM, features disease pathologies such as fibrosis, myocyte apoptosis, and ischemia [13], and a treatment target for DCM should focus on the damaged myocardium in addition to the valvular disease. Several recent papers reported that myoblast sheets applied to ischemic cardiomyopathy tissue [4, 14] could heal old myocardial infarction (OMI) [15, 16] or DCM [17, 18] in large or small animal models through potent angiogenesis, anti-fibrotic effects, and stem cell recruitment induced by cytokine paracrine effects. Here, we applied this innovative method to a patient in whom pulmonary hypertension was successfully controlled by MVR, to improve the damaged myocardium and maintain it after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Because these cells are of autograft origin, easy to extract and multiply, lack carcinogenic risks, and show wide tolerance to ischemia and excellent intrinsic contractility characteristics, autologous SkMs were the earliest candidates in clinical studies for myocardial repair (Menasche et al, 2003; Smits et al, 2003). It has been demonstrated that SkMs partially survive after being transplanted into infarcted myocardial tissue and improve LV function (inhibit LV dilation, increase contractility, and EF) and reverse LV remodeling (Saito et al, 2012; Shirasaka et al, 2016). SkMs ectopically expressed either serine/threonine kinase 1 (Akt‐1) or placental growth factor significantly enhance cardiac function and ventricular remodeling in infarcted heart (Gmeiner et al, 2011; Siepe et al, 2011).…”
Section: Cell Types Used For Cell Therapy Of Cardiac Regenerationmentioning
confidence: 99%